SINERGI KEBIJAKAN REVITALISASI SMK DALAM MENINGKATKAN KOMPETENSI LULUSAN SMK NEGERI 6 PALEMBANG - Abdul Waris (Dharmas Education Journal (DE_Journal), 2020)
This study aims to explain the use of government policy synergies in improving the competence of graduates of SMK Negeri 6 Palembang which include 1) Cooperation between the Business World and the Industrial World, 2) Development and alignment of curriculum, 3) Learning Innovation, 4) Standardization of Facilities and Infrastructure, 5) Management and Institutional Arrangements, and 6) Increasing the Professionalism of Teachers and Education Personnel through the Vocational High School (SMK) revitalization program which is oriented towards graduate competence so that they can be accepted in the Business and Industrial World. One of the recommendations for SMK Negeri 6 Palembang is to continuously evaluate the needs of the Business and Industrial World (DUDI) related to the competencies needed. And this evaluation can be used as a reference for discussing school quality policies in an effort to increase graduate competence.